Eating behavior and body composition across childhood: a prospective cohort study - Ivonne P. M. Derks; Eric J. G. Sijbrands; Melissa Wake; Farah Qureshi; Jan van der Ende; Manon H. J. Hillegers; Vincent W. V. Jaddoe; Henning Tiemeier; Pauline W. Jansen (BMC, 2018)
Abstract Background Although many cross-sectional studies reported that children with overweight or obesity show more food approaching and less food avoidant eating behaviors, there is a lack of replication in longitudinal studies. Therefore, the question remains whether healthcare professionals should target eating behaviors in childhood obesity interventions and prevention. We aimed to examine the longitudinal and possible bi-directional associations between eating behavior and body composition across childhood. Methods Data was included from 3331 children participating in the Generation R Study. At 4 and 10 years, mothers reported on the Child Eating Behavior Questionnaire including the subscales Food Responsiveness, Enjoyment of Food, Emotional Overeating and Satiety Responsiveness, and children's BMI was measured. Body composition, consisting of Fat Mass Index and Fat Free Mass Index was measured at 6 and 10 years with Dual-energy-X-ray-Absorptiometry scans. Results Cross-lagged models including both directions of the BMI - eating behavior association showed that a higher BMI at the age of 4 years predicted more food responsiveness and enjoyment of food and less satiety responsiveness at 10 years (e.g. satiety responsiveness:β = − 0.10, 95% CI = − 0.14, − 0.07), but no associations were found in the opposite direction. For emotional overeating, however, a bi-directional association was found with BMI predicting more emotional eating and vice versa. Multivariable linear regression analyses showed that associations were stronger for Fat Mass Index than for Fat Free Mass Index. Conclusions Results showed that a higher BMI, and particularly higher fat mass, at pre-school age predicted more food approaching and less food avoidant eating behaviors at the age of 10 years, rather than the hypothesized reverse direction. This suggests that increased adiposity in early childhood might upregulate appetite and related eating behaviors.